Young children's access to and use of ICT at home - KLEOPATRA NIKOLOPOULOU; VASILIOS GIALAMAS; MARIA BATSOUTA (Metaichmio Publications, 2010)
This paper investigates young children's access to and use of ICT at home. A questionnaire was completed by the parents of 147 children, aged 4-6,5. Young children have access to and use a wide range of technologies at home, involving domestic leisure technologies, electronic toys and computers. The variables gender, age and parents' educational background had an occassional isolated impact on children's use of ICT. More boys than girls use console games and programmable toys-robots. Parents' high educational background was linked to the use of educational software. Implications for early childhood teachers and links between home and kindergarten are discussed.